woman From the perspective of the German orientalist Anna Marie Schmill -A descriptive analytical study - - Naji, Dr. Zana (Sulaimani Journal for Humanities, 2026)
The German scholar Annemarie Schimmel holds a special place in Arabic literature, and her early works are among the most important in this field. Through them, we discover an aspect that has long been neglected in Arabic studies, taking us on a spiritual and aesthetic journey. She expressed her views on women in Islamic civilization in several places, drawing on her mystical insights. Her mastery of various world languages, including Arabic, Persian, Turkish, Urdu, Pakistani, Punjabi, and Indo-Eastern dialects, allowed her to directly access original sources on women without linguistic barriers or the need for translations. We have followed the descriptive analytical approach, with the aim of analyzing topics related to women from multiple angles, even though this topic has already been discussed by Al-Salmi, Ibn Arabi, Ibn Hazm, Al-Suyuti, and Al-Sakhawi, as most of their teachers were women. Therefore, we saw that the importance of the research for all Kurdish readers does not lie only in the sensitivity of the topic, which Shamil employed in a normal and easy way, but rather in the fact that it is at the forefront of the works that have written about that topic in a dedicated manner and with an intellectual and literary background, using different languages and diverse accents.
Keywords: Woman; Shamil; political activist; good woman; orientalist